Sumbayang Ampek Puluah as A Media of Religious Emansipation of Women Workers in Sijunjung - Jarudin Jarudin; Salma Salma (Jurnal Ilmu Sosial Mamangan, 2020)
This research analyzed the activities and understanding of Muslim women in the Sijunjung area accompanying Ramadan fasting in Sumbahyang Ampek Puluh activities. This religious activity was held in forty days throughout Ramadan Month where 10 days conducted before Ramadhan Month and 30 days in Ramadhan Month. Data were conducted toward observation of Sumbahyang Ampek Puluh activities in 7 Mosques in Sijunjung region during Ramadan Month in 2018 and interviews with several preachers and women of Sumbahyang Ampek Puluh members. Qualitative data analysis was conducted descriptively towards reduction, display and verification. The results show that Sumbahyang Ampek Puluh is dominantly followed by women. These women are at the age of menopause but economically it is still very productive. During the day they work in the fields, gardens, stalls and at night, they stay in the mosque to pray in congregation, pick up the congregational prayers that are left behind, read and study the Qur'an, study Fiqh, interpret the Qur'an and the problems of monotheism, never leave the prayer in congregation, stay away from immoral acts and try to get closer (taqarrub) to Allah like men.